2016
DOI: 10.21053/ceo.2015.01375
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Change in Palatal Sensation in Obstructive Sleep Apnea Patients by Using Two-Point Palatal Discrimination

Abstract: Objectives.Patients with obstructive sleep apnea syndrome (OSAS) have impaired responses to inspiratory resistive loading during sleep. This may be due, in part, to a change in the upper airway sensation. Therefore, we hypothesized that patients with OSAS have diminished upper airway sensation due to snoring.Methods.A total of 53 participants were selected based on clinical evaluation and polysomnography. Two-point discrimination was measured with modified calipers in the tongue and soft palate.Results.A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…They reported a two-point discrimination threshold of 2.5 mm for the early diagnosis of probable soft palate peripheral neuropathy in OSAS patients. 26 We consider that the drying effect of mouth breathing may mean that odours do not dissolve in the saliva and mucus, and this may be another reason for taste disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a two-point discrimination threshold of 2.5 mm for the early diagnosis of probable soft palate peripheral neuropathy in OSAS patients. 26 We consider that the drying effect of mouth breathing may mean that odours do not dissolve in the saliva and mucus, and this may be another reason for taste disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the soft palate was larger in OSAHS than non-OSAHS patients ( Lowe et al, 1996 ), and has been shown to play a key role in OSAHS ( Bacon et al, 1990 ). In addition, fatty infiltration (regardless of obesity status) ( Zohar et al, 1998 ) impairs soft palate sensation, which correlates with the severity of snoring ( Jeong et al, 2016 ); the soft palate becomes altered and exhibits a fiber-type appearance caused by the additional load on the velopharyngeal muscles ( Lindman & Stal, 2002 ) in OSAHS patients. These factors may affect compliance of the soft palate and can cause narrowing of the upper airway.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the soft palate was larger in OSAHS than non-OSAHS patients (Lowe et al 1996), and has been shown to play a key role in OSAHS (Bacon et al 1990). In addition, fatty infiltration (regardless of obesity status) (Zohar et al 1998) impairs soft palate sensation, which correlates with the severity of snoring (Jeong et al 2016); the soft palate becomes altered and exhibits a fiber-type appearance caused by the additional load on the velopharyngeal muscles (Lindman & Stål 2002) in OSAHS patients. These factors may affect compliance of the soft palate and can cause narrowing of the upper airway.…”
Section: )mentioning
confidence: 99%